Disability and disaster risk reduction as an incongruent matrix: Lessons from rural Zimbabwe - Lunga, Wilfred (Jamba, 2019)
The policy thrust of disaster risk reduction initiatives is in many instances tailored towards able-bodied people. This is at the expense of those challenged in many facets such as physically, mentally and other forms of disability. The suggestion for disability to be mainstreamed into disaster risk reduction initiatives has been made imperative by the late shift in hazard and disaster thinking at local, national and international levels. The increasing intensity and frequency of weather-related hazards and disasters, driven by climate change, has provided fertile ground on which mainstreaming ideas and policies have proved to be incongruent. This research paper focuses on two key topics in the disaster science field: pre-disaster risk reduction planning and post-disaster emergency response activities. It is based on experiences from disaster risk reduction projects in Bulilima and Mangwe districts in southern Zimbabwe between 2006 and 2014. A qualitative research methodology was employed, and data were collected using in-depth personal interviews, observations and focus group discussions. Both able-bodied people and people living with disabilities (PWDs) were part of the study. Main findings show that PWDs were not included in the formulation of disaster risk reduction measures. Other important findings were the variable nature of how people define or view disability, and even believe that disability has a purpose. Most of the so-called normal people lack the understanding of what constitutes a disaster to such an extent that even disability is regarded as a disaster. The paper unravels the need to have a relook that would bring PWDs into the centre of civil protection decision-making and policy formulation in Zimbabwe. Keywords: disability; disaster risk reduction; disaster; vulnerability; Zimbabwe.